Adsorption of strontium and caesium onto an Na-illite and Na-illite/Na-smectite mixtures: Implementation and application of a multi-site ion-exchange model. (December 2018) - Siroux, Brice; Wissocq, Aubéry; Beaucaire, Catherine; Latrille, Christelle; Petcut, Cristina; Calvaire, Jordan; Tabarant, Michel; Benedetti, Marc F.; Reiller, Pascal E.
Abstract: The application of a multi-site ion-exchange (MSIE) model to the prediction of contaminant behaviour onto soils or sediments requires a coherent adsorption database. Following the same approach exposed in preceding works on smectite (Siroux et al., Appl. Geochem. 87, 167; Wissocq et al., Appl. Geochem., 93, 167), a database is here implemented to allow modelling the adsorption of radionuclides 90 Sr and 137 Cs onto Na-illite, one of the major clay mineral encountered in the terrestrial environment. This database allows describing the adsorption properties of Sr 2+ and Cs + competing with major cations H + — considered as the reference cation — and Na + onto an Na-illite. To obtain the adsorption site capacities and selectivity coefficients of illite sites for Na + towards H +, a saturation curve of Na + on Na-conditioned illite was acquired. Adsorption isotherms issued from literature have been reinterpreted using the MSIE model to obtain the adsorption properties of Sr 2+ and Cs + onto purified and Na-conditioned illite. Afterwards, the predictability and robustness of the database were verified simulating experimental adsorption of Sr 2+ and Cs + onto Na-illite/Na-smectite mixtures. Graphical abstract: Highlights: Adsorption database for ion-exchange of Sr 2+ and Cs + onto clay minerals is implemented for Na-illite. Site concentrations and selectivity coefficients are fitted from literature and new experimental data. The obtained parameters are used to simulate adsorption behaviours of Sr 2+ and Cs + onto Na-illite/Na-smectite mixtures. Database robustness is verified despite a slight overestimation of Cs + adsorption for high illite content in mineral mixtures.